Central sensitivity to thyroid hormones is reduced in youths with overweight or obesity and impaired glucose tolerance - Di Bonito, Procolo; Corica, Domenico; Licenziati, Maria Rosaria; Di Sessa, Anna; Miraglia del Giudice, Emanuele; Faienza, Maria Felicia; Calcaterra, Valeria; Franco, Francesca; Maltoni, Giulio; Valerio, Giuliana; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2023)
BACKGROUND Thyroid hormones play multiple effects on glucose metabolism. Some recent studies carried out in adult patients suggested an association between altered sensitivity to TH and type 2 diabetes, obesity, and metabolic syndrome. No studies are currently available on the presence of altered sensitivity to the action of TH in youths with prediabetes. OBJECTIVE To evaluate the relationship between sensitivity to TH and impaired glucose tolerance (IGT), impaired fasting glucose (IFG), or glycosylated hemoglobin (HbA1c) ≥ 5.7% in youths with overweight/obesity (OW/OB). MATERIAL AND METHODS This cross-sectional study included 805 Caucasian youths with OW or OB (aged 6-18 years) recruited at seven Italian centers for the care of OW/OB. Individuals with TH out of the normal range of TH in each center were excluded. The fT3/fT4 ratio was evaluated to assess peripheral sensitivity, while TSH index (TSHI), Thyrotroph T4 Resistance Index (TT4RI), Thyroid Feedback Quantile-based Index (TFQI) and Parametric TFQI were calculated to assess central sensitivity. RESULTS Youths with IGT (n =72) showed higher levels of TSH (3.08±0.98 vs 2.68±0.98 mIU/L, P =0.001), TSHI (3.06±0.51 vs 2.85±0.53, P =0.001), TT4RI (46.00±17.87 vs 38.65±16.27, P <0.0001), TFQI [1.00 (0.97-1.00) vs 1.00 (0.99-1.00)], P=0.034), PTFQI (0.67±0.20 vs 0.60±0.22, P =0.007) compared to youths without IGT (n =733), independently of centers and age. No differences were observed for fT3/fT4-ratio. The others phenotypes of prediabetes were not associated with altered sensitivity to TH. Odds ratio of IGT raised of 1-7-fold for each increase of 1 mIU/L in TSH (P =0.010), 1 unit in TSH Index (P =0.004), TT4RI (P =0.003) or PTFQI (P =0.018), independently of centers, age, and prepubertal stage. CONCLUSIONS IGT was associated with a reduced central sensitivity to TH in youths with OW/OB. Our finding suggests that IGT phenotype, known to be associated with an altered cardiometabolic risk profile, might also be associated with an impaired TH homeostasis in youths with OW/OB.